The myth of prison rape: sexual culture in American prisons - Fleisher, Mark S. (Rowman & Littlefield, 2009)
Introduction -- Literature review -- Research design and methodology -- Learning the rules of prison culture -- Prison sexual culture -- The culture of sexual victimization -- Safe zones -- Sex and prison safety